Development and Evaluation of a Portable Visual Stimulus Rebound Board for Table Tennis Training - Alit Rahmat; Reshandi Nugraha; Regi Dwi Septian; Muhammad Zaky Al Ghifary (Sakura Digital Nusantara, 2026)
Purpose: This study aims to design, develop, and evaluate the feasibility of a visual stimulus based portable table tennis rebound board. This instructional media was developed to facilitate students' independent practice and help improve visual focus and stroke accuracy during table tennis lessons in schools. Methods: The research method used is Research and Development (R&D), referring to the 10 step Borg and Gall model. This study involved a sample of 76 participants selected through purposive sampling, divided into three progressive testing phases: (1) preliminary field testing on 6 students (n = 6), (2) main field testing on 30 students (n = 30), and (3) final operational field testing on 40 participants (n = 40) consisting of 12th grade students. Prior to the field trials, the media was evaluated by a validator panel comprising 4 experts (n = 4), namely 2 media/technical experts and 2 subject matter/instructional experts. Data were collected using a questionnaire instrument consisting of 20 statements on a 5 point Likert scale, alongside open ended feedback forms. Quantitative data were analyzed using descriptive percentages and standard deviation (SD), while qualitative data were analyzed through response frequency grouping. Findings: The application of a coordinated target area consisting of 12 target boxes with a high-contrast zig-zag design consistently improved the media's feasibility score across all stages. Quantitative assessment began with expert validation, yielding an average score of 78.75% (± 3.25%) from media/technical experts (